Body Posture Stability in Ski Boots Under Conditions of Unstable Supporting Surface - Tchórzewski, Dariusz (Akademia Wychowania Fizycznego w Katowicach, 2013)
The authors attempted to determine whether: (1) there are differences in stability between the conditions of standing in ski boots and barefoot, (2) the type of surface affects stability, and, (3) the level of stability differs between the frontal and sagittal planes. The study included 35 young male recreational skiers aged 20.71 ±0.63 years. Measurements of stability were taken by means of a Libra seesaw balance board. The conditions of soft surface were created by attaching an inflated cushion to the board. The experiment was carried out on both rigid and soft surface for both movement planes and two different conditions: maintaining the seesaw balance board in the horizontal position and performance of a particular balancing task. All the tests were performed with visual feedback. Restricted ankle joint mobility that results from wearing ski boots caused a reduction of stability in studied subjects, particularly in the sagittal plane. The differences found in the study were likely to be caused by the difficulty the beginners experienced in re-organizing muscular coordination in hip joint strategy and effectively using mechanical support of ski boots that reduces lower limb muscle tone. The use of the soft surface improved stability exhibited by the subjects in the frontal plane without compromising the stability in the sagittal plane. The soft surface might have contributed to a reduction in excessive corrective movements, thus improving stability in studied subjects. The aim of this study was to determine the effect of limitation of foot mobility and disturbances in afferent information from the plantar mechanoreceptors due to wearing ski boots on the level of postural stability in beginner skiers under conditions of the unstable support surface.